A Grave-Marker at Kirby Hill, North Riding. (1st January 2021) - Wood, Rita
Abstract: The grave-marker has recently been mounted with three other pre-Conquest stones in the tower-space at the church of All Saints, Kirby Hill. Only the best-preserved face of the stone can be seen, but this is of more than local interest, since its two motifs suggest some cultural connections across the apparent barrier of the Norman Conquest.